Thermal stability of CVI and MI SiC/SiC composites with Hi-Nicalon™-S fibers. Issue 8 (July 2022) - Bhatt, R.T.; Sola-Lopez, F.; Halbig, M.C.; Jaskowiak, M.H.
Abstract: The influence of high-temperature argon heat-treatment on the microstructure and room- temperature in-plane tensile properties of 2D woven CVI and 2D unidirectional MI SiC/SiC composites with Hi-Nicalon™-S SiC fibers was investigated. The 2D woven CVI SiC/SiC composites were heat-treated between 1200 and 1600 °C for 1- and 100-hr, and the 2D unidirectional MI SiC/SiC composites between 1315 and 1400 °C for up to 2000 hr. In addition, the influence of temperature on fast fracture tensile strengths of these composites was also measured in air. Both composites exhibited different degradation behaviors. In 2D woven CVI SiC/SiC composites, the CVI BN interface coating reacted with Hi-Nicalon™-S SiC fibers causing a loss in fast fracture ultimate tensile strengths between 1200 and 1600 °C as well as after 100-hr isothermal heat treatment at temperatures > 1100 °C. In contrast, 2D unidirectional MI SiC/SiC composites showed no significant loss in in-plane tensile properties after the fast fracture tensile tests at 1315 °C. However, after isothermal exposure conditions from 1315° to 1400°C, the in-plane proportional limit stress decreased, and the ultimate tensile fracture strain increased with an increase in exposure time. The mechanisms of strength degradation in both composites are discussed. Highlights: Determining intrinsic thermal stability of CVI and MI SiC/SiC composites with Hi-Nicalon-S fibers at temperatures to 16000C in argon. Determining the strength and microstructural stability, and failure mechanisms of the composites. Understanding the influence of residual stress on in-plane tensile properties. Suggesting possible methods of improving thermally stability CVI SiC/SiC composites with Hi-Nicalon-S fibers.